Pulmonary Function Testing in Work-Related Asthma: An Overview from Spirometry to Specific Inhalation Challenge - Poussel, Mathias (Int J Environ Res Public Health, 2021)
Work-related asthma (WRA) is a very frequent condition in the occupational setting, and refers either to asthma induced (occupational asthma, OA) or worsened (work-exacerbated asthma, WEA) by exposure to allergens (or other sensitizing agents) or to irritant agents at work. Diagnosis of WRA is frequently missed and should take into account clinical features and objective evaluation of lung function. The aim of this overview on pulmonary function testing in the field of WRA is to summarize the different available tests that should be considered in order to accurately diagnose WRA. When WRA is suspected, initial assessment should be carried out with spirometry and bronchodilator responsiveness testing coupled with first-step bronchial provocation testing to assess non-specific bronchial hyper-responsiveness (NSBHR). Further investigations should then refer to specialists with specific functional respiratory tests aiming to consolidate WRA diagnosis and helping to differentiate OA from WEA. Serial peak expiratory flow (PEF) with calculation of the occupation asthma system (OASYS) score as well as serial NSBHR challenge during the working period compared to the off work period are highly informative in the management of WRA. Finally, specific inhalation challenge (SIC) is considered as the reference standard and represents the best way to confirm the specific cause of WRA. Overall, clinicians should be aware that all pulmonary function tests should be standardized in accordance with current guidelines.